Empowering Vocational Educators in Kulon Progo: IoT and Digital Transformation Training for Enhanced Teaching Skills - Fauziyyah, Anni Karimatul; Subardono, Alif; Rosyid, Nur Rohman; Adrian, Ronald; Oktiawati, Unan Yusmaniar; Putri, Tika Erna; Santoso, Ardhi Wicaksono; Saputra, Yuris Mulya (Universitas Negeri Semarang, 2024)
The IoT (Internet of Things) and Digital Transformation - Skill For All (SFA) training for vocational school teachers in Kulon Progo is an information technology training program. The SFA training addresses the skills gap by offering knowledge and skills necessary to work with IoT devices using IoT Kits from the Network Technology and Application lab, which is evolving in the digital transformation era. This training provides a solid foundation for managing IoT devices, which are highly relevant to today's industry needs. Configuring, managing, and programming IoT devices is essential in the digital age. By participating in this training, vocational school teachers in Kulon Progo can acquire practical skills directly applicable to their curriculum, helping students understand IoT concepts more deeply and practically. The IoT (Internet of Things) and Digital Transformation - Skill For All (SFA) training is designed to provide a comprehensive understanding of networking basics and how to configure and manage IoT Kits devices